(untitled) - Hobbs, Joseph J. (Australia, 2007)
FUNDAMENTALS OF WORLD REGIONAL GEOGRAPHY offers a comprehensive look at world geography. After an introduction, each chapter focuses on one of the eight world regions, describing the historical, cultural, economic, political, and physical aspects that create regional unity, give them personality, and make them newsworthy. The final section of each regional chapter looks at numerous specific issues and landscapes within the region that have broad implications for the rest of the region as a whole and demonstrates how those issues impact other global regions.
Keywords: Geography,Geography